2020
DOI: 10.1038/s41593-020-00719-y
|View full text |Cite
|
Sign up to set email alerts
|

Edge-centric functional network representations of human cerebral cortex reveal overlapping system-level architecture

Abstract: Network neuroscience has relied on a node-centric network model in which cells, populations, and regions are linked to one another via anatomical or functional connections. This model cannot account for interactions of edges with one another. Here, we develop an edge-centric network model, which generates the novel constructs of "edge time series" and "edge functional connectivity" (eFC). Using network analysis, we show that at rest eFC is consistent across datasets and reproducible within the same individual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
355
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(377 citation statements)
references
References 123 publications
22
355
0
Order By: Relevance
“…Recently, we presented a method for decomposing FC into its framewise (instantaneous) contributions [19, 23]. Our work, in agreement with other recent studies [3, 4, 6, 7], demonstrated that all frames do not contribute equally to FC – rather only a small number of high-amplitude frames – “events” – when averaged together, are necessary for explaining a high proportion of variance in FC.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, we presented a method for decomposing FC into its framewise (instantaneous) contributions [19, 23]. Our work, in agreement with other recent studies [3, 4, 6, 7], demonstrated that all frames do not contribute equally to FC – rather only a small number of high-amplitude frames – “events” – when averaged together, are necessary for explaining a high proportion of variance in FC.…”
Section: Discussionsupporting
confidence: 86%
“…Here, we address these questions directly. Our approach leverages a recently-proposed method for decomposing FC into its framewise contributions, detecting events, and assessing the impact of events on timeaveraged FC [19,[23][24][25][26]. We apply this framework to two independently acquired datasets: the Midnight Scan Club [11,12] and the MyConnectome project [10,27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Faskowitz et al [51] have noted that the traditional metric of functional connectivity should be complemented by more complex edge weights and introduced an edge-centric measure. Here we have proposed Ricci-Forman-curvature as an alternative concept.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we suggested a new approach to functional connectivity, by focusing on the dynamics and networks formed by “ edge time series ” (Esfahlani et al, 2020 ; Faskowitz, Esfahlani, Jo, Sporns, & Betzel, 2020 ; Jo, Faskowitz, Esfahlani, Sporns, & Betzel, 2020 ). The approach unwraps time-averaged FC into time series of co-fluctuating signals on network edges resolved at the timescale of single frames in MRI acquisition, thus allowing inspection of network dynamics at fine timescales.…”
Section: Introductionmentioning
confidence: 99%